Răspuns :
[tex] {(x - 1)}^{2} - 4 = 0[/tex]
[tex] {x}^{2} - 2x + 1 - 4 = 0[/tex]
[tex] {x}^{2} - 2x - 3 = 0[/tex]
[tex] {x}^{2} - 3x + x - 3 = 0[/tex]
[tex]x(x - 3) + x - 3 = 0[/tex]
[tex](x - 3)(x + 1) = 0[/tex]
[tex]x - 3 = 0 = > x = 3[/tex]
[tex]x + 1 = 0 = > x = - 1[/tex]
[tex] {x}^{2} - 2x + 1 - 4 = 0[/tex]
[tex] {x}^{2} - 2x - 3 = 0[/tex]
[tex] {x}^{2} - 3x + x - 3 = 0[/tex]
[tex]x(x - 3) + x - 3 = 0[/tex]
[tex](x - 3)(x + 1) = 0[/tex]
[tex]x - 3 = 0 = > x = 3[/tex]
[tex]x + 1 = 0 = > x = - 1[/tex]
(x-1)^2-4=0 =>x^2-2x+1-4=0 =>x^2-2x-3=0
delta=4+12=16
x1=(2+4)/2=3
x2=(2-4)/2=-1
delta=4+12=16
x1=(2+4)/2=3
x2=(2-4)/2=-1